Tourism investment in Algeria and its impact on the movement of economic development - Said Feitas (Social Empowerment Journal, 2022)
Tourism is one of the most important resources that countries rely on to raise the level of their revenues, and this is due to the extreme importance it acquires, as it is one of the basic resources that push the wheel of development and contribute to raising the national economy. This made many countries pay special attention to this sector. Tourism is no longer just a social phenomenon of interest to some individuals and groups only, but has turned into a group of recreational activities with many dimensions, including economic, social, cultural and others.     It has become a stand-alone export industry, playing an important role in the process of economic development. The tourism sector in Algeria has been neglected for many years, but Algeria's rich natural resources and historical sites give it a strong impetus and give it a competitive advantage. And because the nature of tourism activity affects economic growth through the noticeable increase in the country’s gross domestic product, as it is more flexible in countries that give reliance on tourism as an effective basic sector, while the opposite appears in underdeveloped countries or that do not attach tourism a primary importance in their economy, and may depend on another sector. Moreover, if tourism has contributed a great deal to increasing the economic growth of developed countries, will it serve at the same time the economic development policy in Algeria? What is the role of tourism investment in achieving development? On this basis, our study came as an attempt to define and evaluate tourism investment in Algeria, and to clarify the extent of its importance and its repercussions on the economic, social and other conditions.